1982
DOI: 10.1073/pnas.79.20.6215
|View full text |Cite
|
Sign up to set email alerts
|

Opal suppressor serine tRNAs from bovine liver form phosphoseryl-tRNA.

Abstract: An unusual minor species of bovine liver serine tRNA has previously been isolated, sequenced, and found to suppress the UGA termination codon in protein synthesis in vitro [Diamond, A., Dudock, B. & Hatfield, D. (1981) CeU25, 497-506]. We have now found that this tRNA can be a substrate in a specific phosphorylation reaction in which phosphoseryl-tRNA is formed. Moreover, bovine liver contains a second UGA suppressor serine tRNA (tRNASerA; N is a modified nucleoside) which also forms phosphoseryl-tRNA. The nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 19 publications
2
57
0
1
Order By: Relevance
“…Since this original report, the identity, isolation, and cellular role of PSTK, as well as phosphoseryltRNA [Ser]Sec , have remained largely obscure. The minor phosphoseryl-tRNA and another minor seryl-tRNA identified in bovine, rabbit, and chicken livers that decoded the stop codon UGA (12) were shown to be Sec tRNA [Ser]Sec (13). It was subsequently reported that phosphoseryl-tRNA [Ser]Sec was the intermediate in the biosynthesis of Sec in mammals (21,22) and in bacteria (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this original report, the identity, isolation, and cellular role of PSTK, as well as phosphoseryltRNA [Ser]Sec , have remained largely obscure. The minor phosphoseryl-tRNA and another minor seryl-tRNA identified in bovine, rabbit, and chicken livers that decoded the stop codon UGA (12) were shown to be Sec tRNA [Ser]Sec (13). It was subsequently reported that phosphoseryl-tRNA [Ser]Sec was the intermediate in the biosynthesis of Sec in mammals (21,22) and in bacteria (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 1970, a minor seryl-tRNA was reported to form phosphoseryl-tRNA by a kinase activity from rooster liver (11), and a minor seryl-tRNA from bovine, rabbit, and chicken livers was reported to specifically decode the nonsense codon UGA (12). Although it was subsequently shown that both the minor seryl-tRNA that formed phosphoseryl-tRNA and the one that decoded UGA were the same tRNA (13), it was not known at the time these components were discovered that they played instrumental roles in the biosynthesis of Sec and its incorporation into protein as the 21st amino acid in the genetic code. The minor serine tRNA was subsequently found to be selenocysteyl-tRNA [Ser]Sec (10), but the role of the putative kinase that phosphorylated seryltRNA [Ser]Sec has not been resolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two tRNAsSeT were identical [3] and the primary structure of this tRNA from bovine liver [4] and the tRNA gene structure of chicken were determined [5]. The tRNA plays a suppressor role in in vitro globin synthesis [3], but it is unclear whether phosphoserine on the tRNA is incorporated in a polypeptide chain of protein synthesis. cry1 S-300 and affinity chromatography on Blue Sepharose, as one band on disc gels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a kinase that phosphorylated a minor seryltRNA to form O-phosphoseryl-tRNA was reported in rooster liver as early as 1970 [15]. This same year a minor seryl-tRNA from mammalian and chicken liver was found to decode specifically the termination codon, UGA [16], which was subsequently shown to be the same tRNA that formed phosphoseryl-tRNA [17]. This tRNA was subsequently identified as Sec tRNA [Ser]Sec [6].…”
Section: Introductionmentioning
confidence: 99%